The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/apa.13686
|View full text |Cite
|
Sign up to set email alerts
|

Crohn's disease should be considered in children with inflammatory oral lesions

Abstract: The oral manifestations of Crohn's disease might precede intestinal inflammation or coincide with it. Crohn's disease should be considered in children with multiple oral manifestations and paediatric dentists, and gastroenterologists should be involved in their coordinated evaluation and follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 37 publications
0
23
1
2
Order By: Relevance
“…CD is a multifactorial, relapsing inflammatory disease typically affecting the gastrointestinal tract 1. It is a chronic disease with a wide spectrum of clinical manifestations including the involvement of the oral cavity 5. Though the incidence of CD in children of the western countries is stabilising, incidence in the newly industrialised countries increased, ranging from 3 to 30 per 100 000, affecting predominantly the ileum and the colon 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD is a multifactorial, relapsing inflammatory disease typically affecting the gastrointestinal tract 1. It is a chronic disease with a wide spectrum of clinical manifestations including the involvement of the oral cavity 5. Though the incidence of CD in children of the western countries is stabilising, incidence in the newly industrialised countries increased, ranging from 3 to 30 per 100 000, affecting predominantly the ileum and the colon 6.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the nonspecificity of these symptoms, the oral manifestations of CD may not always be carefully evaluated. Especially in children, oral manifestations of CD may precede or coincide with intestinal symptoms and can serve as an important indicator for early diagnosis in this regard 5…”
Section: Introductionmentioning
confidence: 99%
“…Oral manifestations of Crohn's disease are common. A systematic review of 28 articles revealed that oral lesions occur in 10%‐80% of children with Crohn's disease. Lazzerini and colleagues investigated pediatric orofacial granulomatosis and found that 70 of 173 children were also diagnosed with Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Seit damals ist eine Reihe von Fallberichten über Patienten erschienen, bei denen die Crohn-Erkrankung auf Grund schwerer oraler Läsionen diagnostiziert werden konnte [11][12][13][14][15][16][17][18]. Eine aktuelle Literaturübersicht zu Morbus Crohn bei Kindern ergab eine Häufigkeit von oralen Läsionen zwischen 10 und 80 % [19].…”
Section: Einführungunclassified